1998
DOI: 10.1159/000020541
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Line-Derived Neurotrophic Factor Stimulates Ureteric Bud Outgrowth and Enhances Survival of Ureteric Bud Cells in vitro

Abstract: Development of epithelial organs requires co-ordinated interactions between epithelial and mesenchymal tissues. Studies using null mutant mice have indicated that the ret receptor and its ligand, glial cell line-derived neurotrophic factor (GDNF), are crucial for initiation of development of the metanephric kidney. However, the role of this signalling system in other branching organs has not been analysed. Here we describe detailed expression studies of ret, GDNF, and a co-receptor for GDNF (GDNFRα) in the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 27 publications
1
57
0
Order By: Relevance
“…Why is Ret signaling specifically required for tip formation? One potential explanation is that it is important for cell survival in the UB tips, (63) but this was not supported by the data, as dying Ret À/À cells were not observed in the tips. Alternatively, Ret mutant cells might have a migration defect and fail to migrate into the tips in response to GDNF.…”
Section: The Role Of Localized Gdnf/ret Signaling In Ureter Formationmentioning
confidence: 71%
See 1 more Smart Citation
“…Why is Ret signaling specifically required for tip formation? One potential explanation is that it is important for cell survival in the UB tips, (63) but this was not supported by the data, as dying Ret À/À cells were not observed in the tips. Alternatively, Ret mutant cells might have a migration defect and fail to migrate into the tips in response to GDNF.…”
Section: The Role Of Localized Gdnf/ret Signaling In Ureter Formationmentioning
confidence: 71%
“…(10) Addition of GDNF to kidney cultures can increase the number of UB tips, which suggested a stimulation of branching. (42,62) Conversely, GDNF antibodies (42,63) or a Ret-Ig fusion protein (64) inhibit growth of the kidney in vitro. Finally, GDNF is continuously required (but is not sufficient) for the branching of isolated UBs grown in Matrigel with conditioned medium from a mesenchymal cell line.…”
Section: The Role Of Localized Gdnf/ret Signaling In Ureter Formationmentioning
confidence: 99%
“…Cells from all cultures appeared uniformly "mesenchymal" in shape, with irregular, elongated outlines; although uncloned, this phenotype was maintained for more than 20 passages. The mesenchymal phenotype of the cells was further examined by assessing the expression of proteins characteristic of this lineage in vivo (Figure 5A), including the WT1 (21) and PAX2 transcription factors (21), HGF (22) and GDNF (23). All lines expressed GDNF, as assessed by Western blot, with a prominent band at 18 kD ( Figure 5A).…”
Section: Expression Of Ofd1a Protein In Cultured Cellsmentioning
confidence: 99%
“…Gdnf knockout mice are known to have renal agenesis, 2-4 and mice lacking GDNF receptor genes such as Gfra1 5 and Ret 6,7 also exhibit similar phenotypic abnormalities. In vitro studies have also demonstrated that GDNF signaling through GFR␣1 and Ret is a central signaling system involved in both the UB outgrowth from the WD 8,9 and branching morphogenesis of the UB. 10 Nevertheless, a substantial percentage of knockout animals lacking Gdnf (27% 2 ) or its receptors (40 to 45% of Ret Ϫ/Ϫ 7 ) have seemingly normal UB formation, suggesting that the GDNF-dependent budding pathway of the WD may be bypassed by activation of other signaling pathways.…”
mentioning
confidence: 99%